Structurally characterised new twisted conformer for cyclen, controlled by metal ion complexation as seen in NiII and CuII complexes with halides and pseudohalides. Issue 1 (24th November 2021) - Verma, Abhineet; Bhuvanesh, Nattamai; Reibenspies, Joseph; Tayade, Sakharam B.; Kumbhar, Avinash S.; Bretosh, Kateryna; Sutter, Jean-Pascal; Sunkari, Sailaja S.
Abstract : Conformational flexibility of cyclen controlled by complexation with Ni(ii ) and Cu(ii ) as evidenced by structural studies. Abstract : Serendipitous self-assembly is a potential approach for achieving structurally versatile and unexpected solids with chosen metal–ligand combinations. Cyclen (1, 4, 7, 10-tetraazacyclododecane) is an interesting flexible molecule, well explored for biological and material applications of its metal complexes. The dihedral angle ( θ ) between four nitrogen atoms of free cyclen is close to 0°. Still, it may vary upon complexation, allowing flexibility to adopt any two conformers, viz., (i) planar and (ii) twisted. The present work establishes the crucial role of metal ions in controlling the conformation adopted by cyclen through metal complexation. SCXRD studies of the complexes of cyclen with Cu II and Ni II with halides and pseudohalides as counterions reveal the existence of a planar conformation ( θ = ∼0–3°) for cyclen in Cu II systems and a highly twisted conformation (hitherto unreported) in Ni II systems ( θ = ∼52–55°). Further, SQUID magnetic studies for the dimeric [Ni1 ] complex reveal antiferromagnetic interactions between the two Ni centres.